The Failure of the First Romanian Central Bank: Bad Design, Bad Luck, or Both? - Tudor Gherasim Smirna (CES Working Papers, 2015)
In this paper we will analyze the failure of the National Bank of Moldavia, a bank that was chartered by the Principality of Moldavia in 1856, to act primarily as a privileged source of liquidity for its economy. Although the project of a state chartered, privileged bank was planned many years in advance by the princes of the Romanian Principalities, the National Bank of Moldavia suspended payments shortly after its establishment, in early 1858, and had its charter revoked. We will discuss, from the point of view of modern monetary thought, the ideas that were advanced in the justification of its creation, and in the rationalization of is failure. We will analyze the structure of the credits and other problems in its balance sheet. Also, we will study the role that the Crisis of 1857, and the already emerging European economic integration, had in its demise.
Keywords: E5; F54; G01; G28; N23; 330; central banking; international relations; government policy; crisis